Development of the Polak model - Nowak, Wioletta (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
The paper presents an analysis of different modifications of the Polak model that serves as the basis of the IMF’s stabilization programs. According to the standard model, control over net domestic credit expansion is the key to stabilizing the balance of payments. In order to achieve the targeted values for the balance of payments and the rate of inflation in the extended Polak model, the authorities have two policy instruments at their disposal, i.e. domestic credit creation and the nominal exchange rate.
Keywords: kredyt krajowy; program stabilizacyjny MFW; kreacja kredytu krajowego; kurs nominalny